Efficiency Analysis of Zakat Institutions Based on The Organizational Cluster in Indonesia: Free Disposal Hull (FDH) Approach - Ryandono, Muhamad Nafik Hadi; Widiastuti, Tika; Qulub, A. Syifaul; Cahyono, Eko Fajar; Mi'raj, Denizar Abdurrahman; Insani, Taqiyah Dinda (Universitas Negeri Surabaya, 2021)
This study aims to analyse the level of efficiency of zakat institutions in Indonesia between 2014 and 2018. Zakat institutions are divided into three clusters based on the organisation's nomenclature: the government, public, and private groups. The division of these clusters aims to see differences in the management of zakat funds between each group. This study uses a quantitative research approach through the Free Disposal Hull (FDH) method to produce a more comprehensive average efficiency estimation than the Data Envelopment Analysis (DEA). The sampling technique is purposive, and there are fourteen research objects observed. The government cluster is the cluster with the highest efficiency value. The private set comes in second, and the public group comes in third ranking. The high score that the government cluster earns is due to their primary business purpose, which focuses on managing zakat funds. The results of this study can be used as references for the policy establishment of zakat institutions in Indonesia.